2011
DOI: 10.1097/mbc.0b013e3283464f53
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of thrombelastography in identifying neurosurgical patients with worse prognosis

Abstract: Coagulopathy in patients with intracranial haemorrhage or traumatic brain injury (TBI) is associated with clinical deterioration and worse outcome. Whole blood viscoelastic haemostatic assays, like thrombelastography (TEG), might aid conventional coagulation assays in identification of patients with worse prognosis. We performed a review of patients (totalling 78 patients) with primary acute intracranial haemorrhage or isolated TBI admitted to a neurointensive care unit (NICU) for more than 24 h during a perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 11 publications
0
43
0
1
Order By: Relevance
“…Interestingly, only two of the patients found to be hypocoagulable on TEG had similar findings of hypocoagulability on conventional assays. [25].…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 95%
“…Interestingly, only two of the patients found to be hypocoagulable on TEG had similar findings of hypocoagulability on conventional assays. [25].…”
Section: Traumatic Brain Injury (Tbi)mentioning
confidence: 95%
“…Interestingly, only 2 of 8 patients with hypocoagulability according to TEG had concurrent coagulopathy according to international normalized ratio, activated PTT, and/or platelet counts, which suggests that VHA values may be more reliable predictors of outcomes than CCTs. 69 Davis et al demonstrated increased platelet ADP and AA receptor inhibition among patients with TBI and showed that ADP inhibition distinguished survivors from nonsurvivors (p = 0.035), which correlated closely with severity of TBI (p = 0.014). 6 These data suggest that VHAs can be used to identify subgroups in the TBI population that would most benefit from earlier targeted therapies.…”
Section: 2660mentioning
confidence: 98%
“…TEG is able to identify all phases of hemostasis, from initial fibrin formation to clot lysis. Prior studies have used TEG upon admission to identify an early hypocoagulable state after TBI [8,20]. The association of TBI and a hypercoagulable state is well established [5,7,10]; however, the onset and duration of the hypercoagulable state is not.…”
Section: Introductionmentioning
confidence: 98%